The Effectiveness of Google Classroom as English Learning Assistance - Cantika Sari Dewi M; Rezki Suci Qamaria (Kontribusi: Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Google classroom is one of online learning medias which is developed by Google. It is an online class that facilitates teacher and students to interact and connected although they are in distinct area. English is one of courses that uses google classroom as an assistance media in learning process. It is caused English learning has a lot of material and needs a lot of practice. Therefore, assistance media is needed as to assist lecturers in transmitting material and organizing student assignments. This study aims to know the effectiveness of google classroom as English learning assistants. This study uses a descriptive quantitative method that would elaborate the effectiveness of google classroom as English learning assistant in student’s perspective through techniques of questionnaires to collect data. The subject of this research is students who actively use google classroom in learning English. Finding revealed that the effectiveness of Google classroom as an English learning assistance is in the medium category. It indicates that the use of google classroom is still not significantly effective in learning English.